PERANAN ADMINISTRASI PERPAJAKAN DALAM MENINGKATKAN EFEKTIVITAS PEMERIKSAAN PAJAK PADA KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK JAWA BARAT I BANDUNG - Surjono, Welly (Jurnal Riset Akuntansi dan Keuangan, 2016)
Abstract. One of the products of tax regulation reform is the modernization of tax administration which includes among others the changes of the original organizational structure based on the type of tax into function, applying integrated tax administration system that can monitor the service process so that the service can be done quickly, transparently and accountability . Identify the problems discussed in this paper is how the administration of taxation, how the effectiveness of tax examination and how the role of tax administration in improving the effectiveness of tax examination At Kanwil DJP Jawa Barat I. The research method that will be used is descriptive method of analysis and verification method of analysis. The analysis tool that will be used is correlation coefficient analysis, coefficient of determination analysis, and t distribution test for hypothesis testing. Administration of taxation has been done to obtain the actual total score of 3199 compared with the ideal total score of 3640, meaning that employees express very well with the tax administration applied. The result of statistical analysis obtained, it shows a strong relationship and direction between tax administration with effectiveness of tax examination, determinant coefficient analysis obtained, it shows that tax administration can increase effectiveness of tax examination. T test results obtained, then accepted and rejected, meaning that tax administration plays a role in improving the effectiveness of tax examination.Keywords: Tax Administration; Tax Examintaion Abstrak. Salah satu produk dari pembaharuan peraturan perpajakan adalah adanya modernisasi administrasi perpajakan yang meliputi antara lain meliputi perubahan struktur organisasi yang semula berdasarkan jenis pajak menjadi fungsi, menerapkan sistem administrasi perpajakan terpadu yang dapat memonitor proses pelayanan, sehingga pelayanan dapat dilakukan dengan cepat, transparan, dan akuntabilitas. Identifikasi masalah yang dibahas dalam penulisan ini adalah bagaimana administrasi perpajakan, bagaimana efektivitas pemeriksaan pajak dan bagaimana peranan administrasi perpajakan dalam meningkatkan efektivitas pemeriksaan pajak Pada Kanwil DJP Jawa Barat I. Metode penelitian yang akan digunakan adalah metode deskriptif analisis dan metode verikatif analisis. Adapun alat analisis yang akan digunakan adalah analisis koefisien korelasi, analisis koefisien determinasi, dan uji distribusi t untuk pengujian hipotesisnya. Hasil penelitian  menunjukkan hubungan yang kuat dan searah antara administrasi perpajakan dengan efektivitas pemeriksaan pajak, analisis  koefisien determinan menunjukkan bahwa administrasi perpajakan dapat meningkatkan efektivitas pemeriksaan pajak. Hasil Uji  t  diperoleh bahwa  administrasi perpajakan berperan dalam meningkatkan efektivitas pemeriksaan pajak.Kata Kunci: Administrasi Perpajakan; Pemeriksaan Pajak